2008
DOI: 10.1016/j.mee.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Large area silicon epitaxy using pulsed DC magnetron sputtering deposition

Abstract: Pulsed DC magnetron sputtering is used for deposition of large area crystalline (200 mm) silicon 100nm thin films. p doped Si substrates are flashed (T s = 900 °C) under high vacuum (5 10-6 Pa) for removing native oxide and restoring surface crystallinity. Subsequent boron doped Si homoepitaxy is obtained at substrate temperature below 500°C for pulse frequency of 150 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Therefore, the search for alternative approaches is an important element in developing a road map for effective low‐cost thin film silicon based photovoltaic technology. Most work in this field exploits chemical vapor deposition at high temperatures for inducing crystallization although previous research has shown hydrogen‐free epitaxial growth to be possible for 100 nm thick film by magnetron sputtering of a c‐Si target . It has to be noted, however, that deposition rates for epi‐growth were rather low, 3 nm/min.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for alternative approaches is an important element in developing a road map for effective low‐cost thin film silicon based photovoltaic technology. Most work in this field exploits chemical vapor deposition at high temperatures for inducing crystallization although previous research has shown hydrogen‐free epitaxial growth to be possible for 100 nm thick film by magnetron sputtering of a c‐Si target . It has to be noted, however, that deposition rates for epi‐growth were rather low, 3 nm/min.…”
Section: Introductionmentioning
confidence: 99%
“…below 500 °C [122] (see Figure 12f,g), high-vacuum electron cyclotron resonance plasma deposition epitaxy with temperatures in the range of 450-525 °C, [123] ion beam epitaxy using temperatures of above 300 °C, [124][125][126][127] electron cyclotron resonance plasma CVD (ECR-CVD) using temperatures as low as 285 °C, [128] laser-enhanced chemical vapor deposition at temperatures as low as 250 °C [129] and plasma-enhanced chemical vapor deposition (PECVD) (see Figure 12b,c) using temperatures in the range of 700 °C and down to 150 °C. [44,79,95,109,[130][131][132] It should be emphasized that PECVD is the only technique that has allowed to produce thick c-Si films at low temperatures.…”
Section: "Bottom-up" Approachesmentioning
confidence: 99%
“…Reproduced with permission. [122] Copyright 2008, Elsevier. a low thermal budget, thick film growth, and excellent crystal quality.…”
Section: "Bottom-up" Approachesmentioning
confidence: 99%
See 2 more Smart Citations